Real options and CEO social connections: The role of financial flexibility - Bhuyan, Md Nazmul Hasan; García-Feijóo, Luis; Rajkovic, Tijana (Journal of Corporate Finance, 2025)
We examine the impact of CEO social connections on the value of real options. Consistent with the benefits of information transmission, reputation, and trust embedded in social connections, we find that CEO social connections act as real option facilitator through improved financial flexibility, alleviating financial constraints. The effect of CEO social connections is stronger for firms with high growth opportunities and when the CEO has a longer-term career horizon and greater ability. CEO social connections have an increasingly stronger impact on the value of real options. Overall, social connections influence the value of real options, a novel finding in the literature.